(untitled) (Al-Qamar, 2021)
Indian Evidence Act 1872 (IEA, 1872) modified as Qānūn-e-Shahādat Order, 1984 (Q.S.O, 1984) was one of the major laws altered in Pakistan with the intention of bringing them in conformity with Islamic injunctions. This study intends to explore whether the provision of the referred law saying: “No confession made to a police officer shall be proved as against a person accused of any offence”, conforms to the Injunctions of Islam? It finds that the referred provision is against Islamic teachings, as it creates suspicion about police officers which is sin. It cannot be presumed that all confessions made to police officers are procured dishonestly or by unfair means. The fact that some elements are founded in police having involvement in corrupt practices of torture may not be applied as a general rule. There are number of honest police officers deserving credit in the context of performing their professional duties.